PENGARUH KUALITAS PRODUK, HARGA DAN REPUTASI MEREK TERHADAP CUSTOMER LOYALTY MELALUI KEPUTUSAN PEMBELIAN MICROSOFT DYNAMIC NAV (STUDI KASUS PD PT. AEVITAS) - Suhariyo Suhariyo (Universitas Mercu Buana, 2013)
Abstract: Research on customer loyalty through purchasing decisions on a softwareproduct has been widely applied. This study aimed to observe the effect of productquality, price and brand reputation on customer loyalty through dynamic purchasingdecisions NAV Microsoft software.Samples taken are population all customers of PT.Consulting Aevitas by 60 respondents. Data were obtained through the censusquestionnaire, ie walk in customers during 2011. Type of research is quantitativedescriptions using Path Analysis.The results of this study is the structural equation model1 shows that the quality of the product has the greatest influence on purchase decisions.While the structural equation model 2 shows that good quality products, prices and brandreputation have no influence on loyalty, however if through the purchase decision, allthree have an influence on customer loyalty.Keywords: Product Quality, Price, Brand Reputation, Purchase Decisions andCustomer Loyalty.